Development of an electrochemical sensor for detection of secondary metabolite quinoline in Ganoderma boninense infected oil palms - Akanbi, Fowotade Sulayman (2018)
The devastating effect of Ganoderma boninense (G. b) infections in oil palms, which leads to low-income revenues, due to the low yield of diseased palms, has driven researchers to look for early diagnostic techniques. The secondary metabolite, quinoline which was reported to be excreted from the oil palms when attacked by G. b can be used to detect the pathogenic fungus. In order to facilitate an indirect early detection of G. b, a new electrode based on functionalized multi-walled carbon nanotube was developed in this study. The development of the new electrode is based on layer-by-layer self-assembly method using activated multi-walled carbon nanotubes (aMWCNTs) as a backbone, for the attachment of other nanomaterials such as gold nanoparticles (AuNPs) and low molecular chitosan nanoparticle (ChTSNPs). The synthesized gold nanoparticles dispersion was characterized using Zetasizer nano series, UV-visible spectroscopy and cyclic voltammetric (CV) technique. The aMWCNTs and prepared nanohybrid materials (AuNPs-aMWCNTs), were characterized with the aid of field emission scanning electron microscope (FESEM), energy dispersive X-Ray (EDX), while ChTSNPs-aMWCNTs and aMWCNTs were characterized utilizing Fourier-transform infrared (FTIR) spectroscopy. The electrode modification process was monitored by FESEM and voltammetric techniques. Secondary metabolites were extracted from healthy and infected oil palm extracts, using ultrasound-assisted extraction (UAE) method. The performance of the developed electrode was optimized and characterized in quinoline using CV and linear sweep voltammetric (LSV) methods. The developed electrode was characterized in the leaves and root extract secondary metabolites using LSV technique under optimized conditions. The results showed that AuNPs of size 49.27nm and polydispersity index (PDI) of approximately 46% was chosen for electrode modification. This is because the PDI is below 50%. The FESEM micrographs show distinction among the pristine MWCNTs, aMWCNTs AuNPs aMWCNTs, bare electrode and the modified electrode. Also, the attachment of the carboxylic group (-COOH) to the walls of MWCNTs and the loading of the ChTSNPs onto the aMWCNTs were confirmed by the FT-IR spectral. The optimized conditions are as follow: 0.20 M citrate buffer, pH 5.5, accumulation potential, -0.52 V, accumulation time, 180 s and scan rate, 0.06 V/s. Under the measured optimal conditions, the anodic peak current (Ipa) is directly proportional to concentration of quinoline, giving rise to the linear regression equation, Ipa (μA) = 0.7684 + 43.197 [Quinoline]/ (μM), coefficient of correlation, R² = 0.9949, with linear range 0.0004 and 0.10 μM, limit of detection (LOD) 3.75 nM and limit of quantification (LOQ) 12.5 nM. The relative standard deviation (RSD) of Ipa of quinoline with single repeatedly used developed electrode was 2.33%, while it retained 91.7% of the current after being kept for twenty days. The evaluated reproducibility RSD for the between developed electrode anodic peak current response to quinoline oxidation was 3.52%. In addition, no apparent interference was observed in the presence of 1000-fold excess inorganic ions and 500-fold excess organics in 10.0 μM quinoline as all the percentage interferences are below ±10%. Furthermore, the newly developed electrode revealed satisfactory Ipa extract secondary metabolite response over the concentration range of 0.1 to 0.5 ppm with the limit of detection (3 S/N) ranging from 7.87 ppb to 18.54 ppb. The RSD value for reproducibility of Ipa across all the secondary metabolites ranges from 0.73% to 29.35%. The 500-fold excess of interfering organic species in 100 ppm extract secondary metabolite averagely exhibited insignificant interference in the detection process. The proposed sensor stands a brighter future in providing a point of care service in the management of BSR disease of oil palms in South East Asia, especially in Malaysia.